Math

posted by .

Perform the multiplication and use the fundamental identities to simplify.

(cotx + cscx)(cotx-cscx)

I know that you have to foil first so

cot^2x - csc^2x and then use the pythagorean identity 1+cot^2u = csc^2u but I do not know how to simplify.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
  2. calculus

    express in sinx 1 1 ---------- + -------- cscx + cotx cscx - cotx and express in cosx 1 + cot x ------- - sin^2x cscx = 1/sinx so what do i do w. that extra one on the top!?
  3. trig

    express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is that right?
  4. drwls

    My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) = (sinx/cosx)*cotx*(1/sinx) "The last steps should be obvious" Not to me. I can convert (sinx/cosx) to …
  5. Pre-Cal

    Perform the multiplication and use the fundamental identities to simplify. (cotx + cscx)(cotx-cscx) I know that you have to foil first so cot^2x - csc^2x and then use the pythagorean identity 1+cot^2u = csc^2u but I do not know how …
  6. Trigonometric Identities

    Which of the following are trigonometric identities, I have narrowed it down to two - (cscx + cotx)^2 = 1 OR sin^2(x)sec^2(x) + 1 = cot^2(x)csc^2(x)
  7. Calculus

    integral of cscx^(2/3)(cot^3)x i know that cot^2x is csc^2(x)-1, but i just don't understand how to solve the cscx^(2/3), any help?
  8. Trig verifying identities

    I am having trouble with this problem. sec^2(pi/2-x)-1= cot ^2x I got : By cofunction identity sec(90 degrees - x) = csc x secx csc-1 = cot^2x Then split sec x and csc-1 into two fractions and multiplied both numerator and denominators …
  9. trig

    verify (csc^4-1)/cot^2x=2+cot^2x So this is what I have so far on the left side (csc^2x+1)(cscx+1)(cscx-1)/cot^2x =(csc^2x+1)(cot^2x)/cot^2x i think I'm doing something wrong. Please help!
  10. Pre-Calculus

    This question has me stuck. Use the Pythagorean identity sin^2 Θ + cos^2 Θ = 1 to derive the other Pythagorean identities, 1 + tan^2 Θ = sec^2 Θ and 1 + cot^2 Θ = csc^2 Θ. Discuss how to remember these …

More Similar Questions